Impact of skeletal muscle loss during conversion therapy on clinical outcomes in lavage cytology positive patients with gastric cancer - Ding, Ping’an; Yang, Peigang; Yang, Li; Sun, Chenyu; Chen, Shuya; Li, Min; Lowe, Scott; Guo, Honghai; Tian, Yuan; Liu, Yang; Zhao, Qun (Frontiers in Oncology, 2022)
Background: The relationship between sarcopenia and clinical outcomes during conversion therapy in patients with lavage cytology positive gastric cancer (GC-CY1) remains unclear. This study aimed to investigate the impact of sarcopenia and skeletal muscle loss on the efficacy of conversion therapy, tumour response and survival in GC-CY1 patients. Methods: Retrospective analysis of data from a prospective trial of conversion therapy conducted between April 2018 and August 2019 in patients with GC-CY1 (NCT03718624). Skeletal muscle index (SMI) was measured at the level of the third lumbar (L3) vertebra and the sarcopenia was defined using published cut-off points in all patients. We defined ΔSMI (%)/50 days above 9.53% for men and ΔSMI (%)/50 days above 8.81% for women as significant muscle loss (SML) and analysed the changes in skeletal muscle during conversion therapy in relation to treatment efficacy, survival and tumour response. Results: Of the 36 patients, 7 patients (19.44%) developed sarcopenia before conversion therapy, 6 (16.67%) developed new sarcopenia after conversion therapy, and 8 (22.22%) developed SML during treatment. Multivariate analysis showed that sarcopenia before treatment [Odds Ratio (OR) =8.923, 95%CI: 1.341-25.321, p=0.002] and SML during treatment (OR=7.803, 95%CI: 1.106-16.189, p=0.001) had a negative impact on the success rate of conversion therapy. Cox multifactorial analysis found that pre-treatment sarcopenia [overall survival (OS): Hazard Ratio (HR) =6.341, 95%CI: 1.269-18.943, p=0.001; progression-free survival (PFS): HR=8.212, 95%CI: 1.569-36.582, p=0.001], newly developed sarcopenia after conversion therapy (OS: HR=3.189, 95%CI: 1.023-9.811, p=0.012; PFS: HR=3.084, 95%CI: 1.042-14.236, p=0.013) and the presence of SML during treatment (OS: HR=10.234, 95%CI: 2.532-54.231, p=0.002; PFS: HR=9.562, 95%CI: 2.341-38.092, p=0.002) were independent risk factor for OS and PFS in GC-CY1 patients. Conclusion: Pre-treatment sarcopenia and the presence of SML during treatment are strongly correlated with the immediate and long-term outcomes of GC-CY1 patients and can be used as imaging markers to predict the treatment efficacy and prognosis of patients in clinical practice.